2018
DOI: 10.1093/femsle/fny164
|View full text |Cite
|
Sign up to set email alerts
|

The influence of sigma factors and ribosomal recognition elements on heterologous expression of cyanobacterial gene clusters in Escherichia coli

Abstract: Cyanobacterial natural products offer new possibilities for drugs and lead compounds but many factors can inhibit the production of sufficient yields for pharmaceutical processes. While Escherichia coli and Streptomyces sp. have been used as heterologous expression hosts to produce cyanobacterial natural products, they have not met with resounding success largely due to their inability to recognize cyanobacterial promoter regions. Recent work has shown that the filamentous freshwater cyanobacterium Anabaena sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…While the currently available data cannot differentiate between a posttranscriptional and posttranslational mechanism, posttranslational regulation of sigma factors, often by anti-sigma factors and/or regulated proteolysis, is common (33). A recent effort at heterologous expression of the full complement of Nostoc 7120 sigma factors in Escherichia coli was unsuccessful in the case of SigJ (34), possibly indicating inherent instability in the absence of some additional factor(s). This lends support to the theory that SigJ may be subject to regulated proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…While the currently available data cannot differentiate between a posttranscriptional and posttranslational mechanism, posttranslational regulation of sigma factors, often by anti-sigma factors and/or regulated proteolysis, is common (33). A recent effort at heterologous expression of the full complement of Nostoc 7120 sigma factors in Escherichia coli was unsuccessful in the case of SigJ (34), possibly indicating inherent instability in the absence of some additional factor(s). This lends support to the theory that SigJ may be subject to regulated proteolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Fortunately, when 12 Anabaena sigma factors were expressed in E. coli, they were capable of initiating transcription under several cyanobacterial promoters. 32 Unlike the utilization of mutant endogenous RpoD that retains only mutants with the desired properties during the highthroughput screening (HTS), the application of compatible TF is slightly like a game of luck. However, some common considerations should be kept in mind to increase the possibility of success.…”
Section: Employing Compatible Heterogeneous Tfsmentioning
confidence: 99%
“…Nostoc PCC 7120 contains twelve sigma factors that regulate gene expression according to environmental conditions [154]. In a recent study, Wells et al [155] tested the sigma factors from Nostoc PCC 7120 in E. coli and observed that several cyanobacterial promoters were able to drive transcription in E. coli only when sigma factors from Nostoc PCC 7120 were co-expressed. Similarly, sigma factors from Bacillus subtilis can be co-expressed in E. coli to construct an orthogonal expression system [156].…”
Section: Known and Novel Tools For Regulating Gene Expression In Cmentioning
confidence: 99%